Concentrations and kinetics of renal biomarkers in dogs with gastric dilatation-volvulus with and without 24-h intravenous lidocaine - Lehmann, Anna; Brunner, Anna; Marti, Eliane; Francey, Thierry; Steinbach, Sarah; Peters, Laureen M.; Adamik, Katja-Nicole (Frontiers in Veterinary Science, 2023)
Background: Gastric dilatation volvulus (GDV) can lead to organ failure including acute kidney injury (AKI). Due to its cytoprotective, antioxidant and anti-inflammatory effects, lidocaine has a potential to prevent AKI in dogs with GDV. Design and Setting: Prospective, observational cohort study in client-owned dogs with GDV. Objective: To determine concentrations of renal biomarkers for AKI in dogs with GDV with and without intravenous (IV) lidocaine therapy. Methods: Thirty-two dogs were randomized to receive either IV lidocaine (2 mg/kg, followed by a lidocaine constant rate infusion at a dose of 50 µg/kg/min over 24 hours; n=17) or no lidocaine (n=15). Blood and urine samples were taken at admission (T0) (only blood), during or immediately after surgery (T1), and 24 (T24) and 48 (T48) hours after surgery. Plasma creatinine (pCr), plasma neutrophil gelatinase-associated lipocalin (pNGAL), urinary NGAL (uNGAL), uNGAL to creatinine ratio (UNCR), and urinary gamma-glutamyl transferase to creatinine ratio (uGGT/uCr) were evaluated. Biomarker concentrations were compared between dogs with and without IV lidocaine and the course of each marker was determined in comparison to its admission value. Results: In the entire population, a significantly higher pCr at T0 (median, 95 umol/L, interquartile range, 82-105) compared with T1 (69 umol/L, 60-78), T24 (63 umol/L, 52-78), and T48 (78 umol/L, 65-87) (P<0.001) was found. Plasma NGAL increased significantly between T0 (5.66 ng/mL, 3.58-7.43) and T24 (7.50 ng/mL, 4.01-11.89) (P=0.006) and T48 (9.86 ng/mL, 5.52-13.92) (P<0.001), respectively. Urinary NGAL increased significantly between T1 (0.61 ng/mL, 0.30-2.59) and T24 (2.62 ng/mL,1.86-10.92) (P=0.001) and T48 (4.79 ng/mL, 1.96-34.97 (P<0.001), respectively. UNCR increased significantly between T1 (0.15 ug/mmol, 0.09-0.54) and T24 (1.14 ug/mmol, 0.41-3.58) (P=0.0015) and T48 (1.34 ug/mmol, 0.30-7.42) (P<0.001), respectively. Concentrations of uGGT/uCr increased significantly from T0 (highest at T24 (6.20 U/mmol, 3.90-9.90) and significantly decreased at T48 (3.76 U/mmol, 2.84-6.22) (P<0.001). No significant differences in any renal biomarker concentration were found between dogs with and without IV lidocaine therapy. Conclusion and clinical relevance: Plasma NGAL, uNGAL and UNCR remained increased up to 48 hours post-surgery. No evidence of lidocaine-associated renoprotection was found.